Single-Cell Biochemical Multiplexing by Multidimensional Phasor Demixing and Spectral Fluorescence Lifetime Imaging Microscopy - Haas, Kalina T.; Fries, Maximilian W.; Venkitaraman, Ashok R.; Esposito, Alessandro (Frontiers in Physics, 2021)
Revealing mechanisms underpinning cell function requires understanding the relationship between different biochemical reactions in living cells. However, our capabilities to monitor more than two biochemical reactions in living cells are limited. Therefore, the development of methods for real-time biochemical multiplexing is of fundamental importance. Here, we show that data acquired with multi-colour (mcFLIM) or spectrally-resolved (sFLIM) fluorescence lifetime imaging can be con-veniently described with multi-dimensional phasor transforms. We demonstrate a computational framework capable of demixing three FRET probes and quantifying multiplexed biochemical activi-ties in single living cells. We provide a comparison between mcFLIM and sFLIM suggesting that sFLIM might be advantageous for the future development of heavily multiplexed assays. However, mcFLIM – more readily available with commercial systems - can be applied for the concomitant monitoring of three enzymes in living cells without significant losses.